Pregunta
upstudy study bank question image url

6) \( 27 x^{3}-1=0 \)

Ask by Turnbull Burgess. in the United States
Jan 30,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

\( x = \frac{1}{3} \)

Solución

Solve the equation by following steps: - step0: Solve for \(x\): \(27x^{3}-1=0\) - step1: Move the constant to the right side: \(27x^{3}=0+1\) - step2: Remove 0: \(27x^{3}=1\) - step3: Divide both sides: \(\frac{27x^{3}}{27}=\frac{1}{27}\) - step4: Divide the numbers: \(x^{3}=\frac{1}{27}\) - step5: Simplify the equation: \(\sqrt[3]{x^{3}}=\sqrt[3]{\frac{1}{27}}\) - step6: Calculate: \(x=\sqrt[3]{\frac{1}{27}}\) - step7: Simplify the root: \(x=\frac{1}{3}\) To solve the equation \( 27 x^{3} - 1 = 0 \), we can follow these steps: 1. **Isolate the term with \( x \)**: \[ 27 x^{3} = 1 \] 2. **Divide both sides by 27**: \[ x^{3} = \frac{1}{27} \] 3. **Take the cube root of both sides**: \[ x = \sqrt[3]{\frac{1}{27}} = \frac{1}{3} \] Thus, the solution to the equation \( 27 x^{3} - 1 = 0 \) is: \[ x = \frac{1}{3} \] Alternatively, this can also be expressed as: \[ x = 0.\dot{3} \] Both forms represent the same value.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Extra Insights

To solve the equation \( 27x^3 - 1 = 0 \), we can factor it using the difference of cubes formula, \( a^3 - b^3 = (a-b)(a^2 + ab + b^2) \). Here, we have \( a = 3x \) and \( b = 1 \). Thus, we rewrite the equation as: \[ (3x)^3 - 1^3 = 0 \] Factoring it gives us: \[ (3x - 1)((3x)^2 + 3x \cdot 1 + 1^2) = 0 \] This breaks down to: \[ (3x - 1)(9x^2 + 3x + 1) = 0 \] Setting each factor to zero, we first solve \( 3x - 1 = 0 \), leading to \( x = \frac{1}{3} \). The other factor, \( 9x^2 + 3x + 1 = 0 \), can be solved using the quadratic formula \( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \). Substituting \( a = 9, b = 3, c = 1 \): \[ x = \frac{-3 \pm \sqrt{3^2 - 4 \cdot 9 \cdot 1}}{2 \cdot 9} = \frac{-3 \pm \sqrt{9 - 36}}{18} = \frac{-3 \pm \sqrt{-27}}{18} = \frac{-3 \pm 3i\sqrt{3}}{18} = \frac{-1 \pm i\sqrt{3}}{6} \] So, the complete solutions for the equation \( 27x^3 - 1 = 0 \) are: \[ x = \frac{1}{3}, \quad x = \frac{-1 + i\sqrt{3}}{6}, \quad x = \frac{-1 - i\sqrt{3}}{6} \] Now, that's a sweet mix of real and complex numbers!

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad